Frailty and GLIM-defined malnutrition contribute to poor clinical outcomes in older adult inpatients in the general surgery department - Liu, Chengyu; Chen, Liru; Liu, Peng; Li, Lei; Cheng, Bo; Xu, Jingyong; Cui, Hongyuan; Zhu, Mingwei (Frontiers in Nutrition, 2025)
Background and aimsFrailty and malnutrition are prevalent among older adult inpatients. Our study aimed to analyze the correlation between frailty and malnutrition and determine their effects on the clinical outcomes in older adult surgical inpatients.MethodsThis cross-sectional observational study included older adult inpatients (≥ 65 years old) undergoing scheduled surgery. Anthropometric measurements and hematological examination results were collected at the time of admission. Frailty and malnutrition were assessed using the frailty phenotype and the Global Leadership Initiative on Malnutrition (GLIM) criteria. Nutritional support during hospitalization and clinical outcomes, such as the occurrence of postoperative complications, in-hospital death, length of hospital stays, and hospital costs, were recorded. The chi-squared and rank-sum tests were used for comparison. Univariate and multivariate logistic regression analyses were used to calculate the odds ratios (OR) and 95% confidence intervals (CI) for frailty, malnutrition, and postoperative complications.ResultsIn 394 patients, the frailty prevalence was 17.3% (68/394), and 146 inpatients (37.1%) were malnourished. The overlapping prevalence rate of frailty and malnutrition was 12.2% (48/394). Frailty and malnutrition were correlated (r = 0.464, p < 0.001). Multivariate analysis revealed that frailty significantly increased the risk of postoperative complications (OR: 2.937, 95% CI: 1.475–5.850, p = 0.002). There were significant differences in the length of hospital stays and hospital costs among the four groups of patients with frailty and malnutrition, frailty and no malnutrition, malnutrition and no frailty, and no frailty and malnutrition (p < 0.001; p < 0.001).ConclusionA significant positive correlation was observed between frailty and malnutrition. Frailty and malnutrition are significantly associated with adverse clinical outcomes. Therefore, it is necessary to manage frailty and malnutrition to improve the prognosis.